The Effectiveness and Clinical Usability of a Handheld Information Appliance - Patricia A. Abbott (Nursing Research and Practice)
Clinical environments are complex, stressful, and safety critical—heightening the demand for technological solutions that will help clinicians manage health information efficiently and safely. The industry has responded by creating numerous, increasingly compact and powerful health IT devices that fit in a pocket, hook to a belt, attach to eyeglasses, or wheel around on a cart. Untethering a provider from a physical “place” with compact, mobile technology while delivering the right information at the right time and at the right location are generally welcomed in clinical environments. These developments however, must be looked at ecumenically. The cognitive load of clinicians who are occupied with managing or operating several different devices during the process of a patient encounter is increased, and we know from decades of research that cognitive overload frequently leads to error. “Technology crowding,” enhanced by the plethora of mobile health IT, can actually become an additional millstone for busy clinicians. This study was designed to gain a deeper understanding of clinicians’ interactions with a mobile clinical computing appliance (Motion Computing C5) designed to consolidate numerous technological functions into an all-in-one device. Features of usability and comparisons to current methods of documentation and task performance were undertaken and results are described.